A commercial approach to solar power distribution in India. (1st January 2003) - Bhattacharjee, Chitta Ranjan
In India, approximately 5, 000 of 79, 000 unelectrified villages, either unapproachable from the grid line or subject to uneconomic viability, are awaiting electricity through SPV power as the only suitable technological option. SPV power, which is expensive in capital cost, although affordable in tariff, is on successful trial through a novel scheme that is subsidy-free. Limited scale applications, with ten plants of 25-50 kW capacities in successful operation, are situated at Sagardweep, an island in southern West Bengal in India. The objective is to improve the quality of living standards there. The cost of energy per kWh is approximately $0.16. No doubt this is high, considering the grid tariff is less than 50% but it is acceptable to people in the context of the scarcity, high price and inconvenience associated with kerosene or diesel fuel as the only alternative energy resources.